Leveraging Medical Students’ Experiences with Social Determinants of Health During Their Pediatric Clerkship to Drive Curriculum - Shashwat Kala; Rachel Johnson; Uma Phatak; Ada Fenick; Michael Goldman (Journal of Medical Education and Curricular Development)
Background The relationship between social determinants of health (SDH) and negative health outcomes is well established, prompting undergraduate medical educators to teach students to recognize and address these SDH. However, current SDH resources like the Healthy People 2030 report and published curricula lack a targeted approach to best teach and learn pediatric-specific SDH. Objective To use medical students’ experiences working with patients affected by SDH on their pediatric clerkship as a targeted needs-assessment to drive pediatric-specific SDH curricula. Methods Qualitative analysis of the reflective journal entries of 94 medical students who rotated on the pediatrics clerkship from 2022–2023. Each student completed an entry on their experiences with pediatric SDH including identification of the SDH, perceptions of the impact of the SDH, and observed SDH navigation strategies. A team of three coders employed both deductive and inductive content analysis to the dataset. SDH codes were tabulated for frequency analysis. Findings Across the 94 entries, there were 205 reported SDH, with an average of 2.18 SDH per entry. Inductive content analysis resulted in six new pediatric-specific SDH in addition to those established by Healthy People 2030 report. Our analyses showed that students perceived SDH to impact pediatric patients and their families through five mechanisms; analyses of student entries also identified five strategies that the healthcare team used to facilitate SDH navigation. Finally, a frequency analysis showed that the three most common SDH clerkship students experienced were Language & literacy, Foster care / Department of Children and Families (DCF) system, and Insurance status. Conclusion Utilizing the medical student experience with SDH on the pediatric service can serve as a meaningful needs-assessment to drive pediatric-specific SDH curricular development. We identified a unique set of pediatric-specific SDH that may improve medical schools’ SDH curricula.